Challenges of the International Baccalaureate Middle Years Programme: Insights for school leaders and policy makers - Dickson, Anisah; Perry, Laura; Ledger, Susan (Education Policy Analysis Archives, 2021)
Policy makers in the US and several other countries are recommending that more schools offer an International Baccalaureate (IB) programme. However, little is known about the challenges that IB programmes present for teaching and learning particularly those meeting national curriculum. In this study, we examined the challenges of the IB’s Middle Years Programme (MYP), the least understood and researched of the IB programmes. Using a qualitative case study design, we conducted in-depth and semi-structured interviews with school leaders (n=7) and teachers (n=10) from three schools in Australia that previously offered the MYP. We used thematic analysis to generate the findings and the IB’s Standards and Practice framework to organize the reporting of findings. Participants shared perceived challenges related to philosophical factors, organizational dilemmas and complexities with integrating the MYP with Australia’s national curriculum. Understanding the organizational and leadership challenges that schools may face when offering the MYP can help policy makers promote the necessary conditions for successful program implementation.